PENGARUH INTELLECTUAL CAPITAL DAN CAPITAL STRUCTURE TERHADAP FINANCIAL PERFORMANCE DENGAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING (Studi pada Subsektor Perbankan yang terdaftar di BEI Tahun 2019-2023) - Bintang Oktafiani; Rosalia Dwi Fadma Tjahjanti (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2025)
This study aims to determine the effect of Intellectual Capital and Capital Structure on Financial Performance with Competitive Advantage as an intervening variable in the banking subsector listed on the IDX in 2019-2023. The study population amounted to 47 annual reports and a sample of 28 banking subsector annual reports taken using purposive sampling technique. The analysis method used is SEM-PLS using WarpPLS 7.0 software. The results showed that intellectual capital has an insignificant effect on competitive advantage, capital structure has a significant effect on competitive advantage, competitive advantage has a significant effect on financial performance, intellectual capital has a significant effect on financial performance, capital structure has a significant effect on financial performance, intellectual capital has an insignificant effect on financial performance through competitive advantage, and capital structure has a significant effect on financial performance through competitive advantage. Keywords: Intellectual Capital, Capital Structure, Competitive Advantage, Financial Performance